Pengenalan Hitung Cepat Untuk Siswa Sekolah Dasar Desa Karanggondang, Mlonggo, Jepara - Maharani Patria Ratna (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2018)
This contribution to society activity’s (KKN) is about Japanese quick count style in Mathematics. The object of this activity is students of Elementary School in Karanggondang village, Mlonggo District, Jepara Regency. This activity is supported by LPPM, lecturer of KKN, and students of KKN. To run this programme, the KKN team is partnered with Karanggondang Elementary school. As a preparation for national exam, this programme is aimed at the students of 5th grade. The output of this activity are video and module.